27. Evaluation of automated planning for VMAT accelerated partial breast irradiation. (December 2018) - Marrazzo, L.; Arilli, C.; Meattini, I.; Casati, M.; Talamonti, C.; Livi, L.; Pallotta, S.
Abstract : Purpose: The quality of accelerated partial breast irradiation (APBI) plans generated by the Auto-Planning (AP) module of the Pinnacle3 (Philips Medical Systems, Fitchburg, WI) treatment planning system was compared to manually generated clinical plans. Methods: Thirty patients treated with APBI for left breast lesions were selected. Ten were used for definition of beam parameters and optimization goals of the AP technique. Subsequently, 20 patients, previously planned with Monaco (Elekta AB, Stockholm, Sweden), were replanned using AP with no further manual intervention. Plans were compared in terms of dosimetric plan parameters, degree of modulation (Modulation Complexity Score, MCS), monitor units (MU) and treatment time, and by blind qualitative scoring by a treating physician. Dosimetric verification was also performed and evaluated in terms of γ passing rate and point dose measurements. Statistical significance of differences was assessed using paired two-sided Wilcoxon signed-rank test. Results: A statistically significant improvement in PTV coverage (p = 0.02) and PTV homogeneity index (p = 0.002) was observed in favor of AP plans compared to manual. Concerning dose to organs at risk, no statistically significant differences were found. A trend toward the reduction in ipsilateral breast V 15 Gy with AP was observed (p = 0.06) (Fig. 1). As reported inTable 1, the modulation degree was reduced using AP compared to manual, as well as MU, while treatment time was slightly increased. No statistically significant differences were observed in γ passing rate. As a result of the blind comparison by the treating physician, in 50% of cases AP was considered superior to manual, with high clinical relevance. In 40% AP was considered better with minor clinical relevance, and in the remaining 10% plans were considered to be equivalent. Conclusions: AP for VMAT APBI is able to produce plans of at least equal quality and overall superior to those obtained with manual planning.